Hubungan Gejala Kecemasan dan Gejala Depresi terhadap Persiapan Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) di Fakultas Kedokteran Universitas Pattimura - Muammar D. Makasar; Bertha J. Que; Johan B. Bension; Laura B. S. Huwae (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Medical students need to take the Competence test as Doctor Profession Program (UKMPPD) to be passed and earned their medical profession. Exams are one of the most common stressors experienced by medical students and the body will respond to these stressors in the form of feelings of depression or anxiety. Anxiety and depression itself can affect student performance during exam preparation. The purpose of this study was to determine the relationship between anxiety and depression on the preparation of the Professional Doctoral Program Competency Test (UKMPPD) for students of the Faculty of Medicine, University of Pattimura. The method used is quantitative analysis with cross sectional research design and total sampling technique. The sample is all the student population of the Faculty of Medicine, University of Pattimura who meet the inclusion and exclusion criteria, totaling 90 respondents. The results showed that the majority of respondents experienced mild anxiety symptoms, which is 37% during the CBT exam and 34% during the OSCE exam. The majority of respondents also did not experience depression, which is 68% during the CBT and 70% during the OSCE and the majority had an optimal level of preparation for UKMPPD, which is 63% during the CBT and 64% during the OSCE. Data analysis using the chi square test showed a significant relationship between anxiety symptom and the level of preparation for UKMPPD both CBT (p=0.030) and OSCE (p=0.012). There was no significant relationship between depression symptom and the level of preparation for UKMPPD for both CBT (p=0.123) and OSCE (p=0.07). It can be concluded that there is a significant relationship between anxiety and preparation for UKMPPD, but there is no significant relationship between depression and preparation for UKMPPD.